Characterization of seahorse (Hippocampus comes L.) extracts originating from culture and nature in Pesawaran, Lampung, Indonesia - Mundijo, Trisnawati; Suyatna, Franciscus Dhyanagiri; Wibowo, Agung Eru; Supriyono, Agus; Midoen, Yurnadi Hanafi (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Indonesia is an archipelagic country with a mega biodiversity, among others, in the marine area. Seahorses (Hippocampus spp.) are a marine fish known to have biocompounds used in traditional medicine “Jamu,” such as Hippocampus comes L. (HCL). The present study aims to analyze and compare the chemical contents of cultured seahorse (CS) and natural seahorse (NS) extracts. Materials and Methods: The CS and NS were identified morphometrically. After freeze-drying, the seahorses were ground into powder with a grinder. The seahorse powder was extracted with ethanol and a water solvent. The extract contained biocompounds, proximate, amino acids, and steroids with high-performance liquid chromatography. Results: The study found unique characteristics of HCL. The highest yield was obtained in NS using a water solvent (18.6%). The biocompounds in seahorses consist of alkaloids and triterpenoids. The highest proximate of water content (11.03%) and ash content (42.50%) was found in NS. In addition, other compounds were also detected in CS, such as fat (7.48%) and protein (47.67%). Both of HCL’s different sources had all essential and nonessential amino acids in which the highest concentration were in NS, i.e., L-arginine (56,537.22 mg/kg), L-lysine (17,794.17), glycine (113,649.80 mg/kg), L-proline (47,056.15), and L-alanine (43,451.81). The analysis of the steroid compound of the extract suggested the presence of steroid glycosides. Conclusion: The highest yield of the seahorse extract with a water solvent is about 18.6% and protein content of 47.67% in CS. The crude extract has alkaloids, triterpenoids, and glycine (113,649.80 mg/kg) in NS with water, suggesting the presence of steroid glycosides. J. Adv. Vet. Anim. Res., 8(4): 610–616, December 2022 http://doi.org/10.5455/javar.2022.i630